Topografia baśniowego pogranicza jako reprezentacja doświadczania zła (na podstawie zbiorów baśni pisarzy polskich) - Ślósarska, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
While reconstructing the subject of fairy-like borderland I consecutively discuss the problems of literary topography as a spatial figure of experiencing evil, next releasing the conflict and creation of domesticated seats and internalization and projection of fairy-like evil. In the conclusion I emphasize the tension between internal and social maturation of the hero and the semantics of the threshold and transgression as a special way of lexical organization of the fairytale form referring these problems onto theoretical and analytical contexts of postmodern culture. Because while being on the borderland fairytale characters experience evil of mainly situational character I accept in my analysis the basic assumptions of the phenomenological- existential philosophy of Gabriel Marcel dealing with the situation in which evil is encountered and experienced by specific subjects.
Topography of fairy-like borderland as representation of experiencing evil (based on collections of fairytales by Polish writers)
Keywords: Marcel; evil; borderland; script; fairy tale; narration; zło; pogranicze; skrypt; baśń; narracja